The Use of the Think-Pair-Share Method to Improve Culinary Arts Students’ Speaking Skill - Hamida Pusparani; Marhum, Mochtar; Maghfira, Maghfira; Hasyim, Zarkiani (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This research focuses on effectiveness of Think-Pair-Share (TPS) method for developing speaking or communicating skills of SMK Negeri 1’s tenth-grade culinary arts students. This research applied a quasi-experimental design with a pair of different kinds of groups: experimental and control. The experimental group was obtained treatment by implementing Think-Pair-Share method, while the conventional approach was used to teach the control group. Pre and post-tests assessed students' speaking skills regarding accuracy, fluency, and comprehensibility. The findings revealed that TPS (Think-Pair-Share) method significantly increased students' speaking proficiency, as seen by a mean score increase in the experimental group from 40.15 to 51.50. The Mann-Whitney test proved major differences between each of the groupings (p < 0.05). Indicating the TPS improves speaking proficiency. The data indicate that TPS (Think-Pair-Share) is such a successful cooperative learning strategy which increases student engagement, reduces speaking fear, and improves communicative competence in English.